Perspectives of practitioners on support for caregivers of children with intellectual disability - Lebogang L. Molefe; Leepile A. Sehularo; Daleen M. Koen (AOSIS, 2024)
Background: Children with profound intellectual disabilities are unable to do anything for themselves and require full-time care in healthcare facilities. While caring for children, secondary caregivers become overwhelmed. Coupled with little or no support, the overwhelming work affects their psychological, social and financial well-being. Mental healthcare practitioners have perspectives on conditions under which secondary caregivers work and how can they be supported. Little is known about such perspectives. Objectives: This study aims to explore and describe the perspectives of mental healthcare practitioners regarding the conditions under which secondary caregivers of children with profound intellectual disabilities work and how can they be supported. Method: A qualitative-exploratory-descriptive and contextual research design was adopted using a non-probability purposive sampling technique. This study was conducted in Gauteng province. Semi-structured individual interviews were performed to collect data. Content data analysis and ATLAS.ti were used to analyse the data. Results: Knowledge and skills development, stress reduction, resources and motivation were themes that emerged. Conclusion: This study explored and described the perspectives of mental healthcare practitioners regarding the conditions under which secondary caregivers of children with profound intellectual disabilities work and how can they be supported. If implemented, perspectives can improve the holistic well-being of secondary caregivers. Contribution: This study broadened an understanding of how secondary caregivers can be supported. Future researchers can use study results to develop programmes, intervention strategies and frameworks to support secondary caregivers.